In vitro propagation of Castanea sativa Mill. - S A, Zakeri; Hashimah, Elias; N. N. H., Mohd Hisham (International Society for Horticultural Science, 2024)
Castanea sativa Mill. commonly known as sweet chestnut is a versatile plant that is typically used as foods, medicines, furniture, outdoor constructions, etc. In southern Europe, Turkey, and southwestern and eastern Asia, it is considered a staple food which made propagation and conservation crucial for the sustainability of the plant. In consequence, the present study attempted to focus on the in vitro propagation of Castanea sativa to meet the industry demand for planting materials. This study aimed to obtain the optimum medium for the production of Castanea sativa Mill. plantlets. Besides, investigated the effects of plant growth regulators and additives either applied singly or in combination on in vitro propagation. Initially, Castanea sativa Mill. seeds were surface sterilized using disinfectant agents before being subjected to MS basal for seed germination. Subsequently, the aseptic seedlings obtained were then excised and cultured in various treatments. After 2 months, observations were recorded on the percentage of explant producing shoots (%), mean number of shoots per explant, mean shoot height (cm), mean number of leaves, and mean leaves length (cm). Results clarified the treatments tested mostly promoted 100% shoot production. Statistical analysis disclosed the most recommended medium for in vitro regeneration of the plant species was MCA + 3.0 mg L-1 BAP + NAA. Anatomical study revealed the stomata dispersion and stomata opening sizes. The present study contributed to a fundamental understanding of in vitro propagation and morphology of C. sativa.